Biobased thin-film composite membranes comprising priamine–genipin selective layer on nanofibrous biodegradable polylactic acid support for oil and solvent-resistant nanofiltration. Issue 13 (22nd June 2022) - Yang, Cong; Topuz, Fuat; Park, Sang-Hee; Szekely, Gyorgy
Abstract : A robust and sustainable thin-film composite membrane, using green raw materials on a highly porous, electrospun and biodegradable support, was developed for molecular sieving. Abstract : Green thin-film composite (TFC) membranes can offer a sustainable solution for the separation of complex mixtures in aqueous and organic solvent nanofiltration (OSN). However, the fabrication of TFC membranes has relied on toxic petrochemical-based monomers, solvents, and supports. Herein, we developed a green TFC membrane using solely sustainable resources. A fully biodegradable electrospun nanofibrous support comprising polylactic acid (PLA) and gelatin (as the interlayer) was developed for the TFC membranes. Dimethyl carbonate and water, as green solvents, were used for the dissolution of PLA and gelatin, respectively. The incorporation of the gelatin interlayer enhanced the hydrophilicity of the support, leading to the homogeneous adhesion of the TFC membrane. Green polyamide TFC membranes were fabricated on the porous support via the interfacial polymerization of natural monomers, namely the plant-based genipin in the aqueous phase, and priamine in the green organic solvent eucalyptol. The biodegradability of the support was demonstrated using proteinase K within 10 h. The green TFC membrane showed outstanding acetone permeance up to 10 L m −2 h −1 bar −1 with a molecular weight cut-off in the range of 178–391 g mol −1 . The optimized membrane demonstrated an oil removal rate of 99.6% in the produced water treatment at a water permeance of 5.6 L m −2 h −1 bar −1 . The robustness of the TFC membrane was evidenced through continuous crossflow filtration under 30 bar over seven days. The sustainability of the membrane was assessed and compared against green and conventional membranes. Overall, the excellent solvent stability and OSN performance of the ecofriendly TFC membranes can lead to new advances in sustainable membrane manufacturing.